Homogeneous ZrO2 gate dielectrics with intermediate ozone oxidation for improved interface stability and leakage suppression in Ge-based MOS devices - Lee, Jongwon; Choi, Hwayong; Heo, Junseok (Materials Science in Semiconductor Processing, 2025)
With recent advances in semiconductor technology, Ge has gained significant attention as a high-mobility channel material. However, integrating Ge with high-k dielectrics remains challenging owing to the formation of unstable Ge suboxides at the interface, which degrade the device performance by increasing the interface trap density and leakage current. This study explores the use of a ZrO2 interlayer, replacing Al2O3, followed by ozone post-oxidation (OPO) and an additional ZrO2 deposition to create a homogeneous ZrO2 gate dielectric on Ge. The resulting ZrO2/OPO/ZrO2 structure effectively suppresses the formation of unstable Ge suboxides, blocks Ge diffusion, and reduces the number of polycrystalline ZrO2 phases. These advantages have been confirmed through extensive material studies including high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray diffraction. The electrical characteristics were examined using capacitance-voltage and current density-voltage measurements. Moreover, the leakage current behavior was further analyzed using current conduction mechanism models. The ZrO2/OPO/ZrO2 stack exhibits a low equivalent oxide thickness (EOT) of 1.87 nm, an interface trap density (Dit) of 2.48 × 1012 cm−1ev−1, and a reduced leakage current density of 7.05 × 10−7 A/cm2 at 1 V. This study highlights the possibility of the ZrO2/OPO/ZrO2 stack as a high-performance gate dielectric for next-generation Ge-based MOS devices.
Keywords: Germaniums (Ge); High- k; High-k/ge MOS; Interface stabilities; Interface trap density; Interface-trap density; Ozone oxidation; Ozone post oxidation; Post-oxidation; ZrO 2; Germanium oxide; High-k/Ge MOS; Ozone post oxidation; ZrO2